Pengaruh Pemberian Kayu Apu (Pistia stratiotes L.) dan Dosis Pupuk N, P , K pada Pertumbuhan dan Hasil Padi Sawah (Oryza sativa L.) - Husni Thamrin Sebayang; Agus Suryanto; Tristi Indah Dwi Kurnia (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
An experiment to study the effect of water lettuce (Pistia stratiotes L.) application and N, P, K fertilizer on growth and yield of rice was carried out on inceptisol soil at Mojosari Research Farm, Mojokerto, East Java, Indonesia, ± 100 m asl, from December 2007 to April 2008. The experiment was arranged in a Split Plot Design with three replications. Water lettuce application as main plot consisted of four treatments, they are: without water lettuce, water lettuce planted in the rice plot, water lettuce incorporated in the soil, and water lettuce applied as compost. Three dosages of N-P2O5 -K2O fertilizer as sub plot consisted of 135-27-30, 101.25-20.25-22.5, and 67.5-13.5-15 kg ha-1. The results showed that the application of 135-27- 30 or 101.25-20.25-22.5 kg N-P2O5 -K2O ha-1 and the application of water lettuce did not signifi cantly affect rice yields. The combination of 135-27-30 or 135-27-30 kg N-P2O5 -K2O of ha-1 and 3 ton water lettuce compost ha-1 increased the growth of rice at 30 days after sowing. Application of water lettuce did not interact with N, P and K fertilizer application in affecting rice yield components.Keywords: fertilizer, low external input, rice, water lettuce